2023
DOI: 10.1001/jamaoncol.2023.1007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity of Olvimulogene Nanivacirepvec–Primed Immunochemotherapy in Heavily Pretreated Patients With Platinum-Resistant or Platinum-Refractory Ovarian Cancer

Abstract: ImportancePatients with platinum-resistant or platinum-refractory ovarian cancer (PRROC) have limited therapeutic options, representing a considerable unmet medical need.ObjectiveTo assess antitumor activity and safety of intraperitoneal (IP) olvimulogene nanivacirepvec (Olvi-Vec) virotherapy and platinum-based chemotherapy with or without bevacizumab in patients with PRROC.Design, Setting, and ParticipantsThis open-label, nonrandomized multisite phase 2 VIRO-15 clinical trial enrolled patients with PRROC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…VIRO-15 is the phase 2 study of clinical activity of olvimulogene nanivacirepvec (Olvi-Vec)-primed immunochemotherapy in heavily pretreated patients with platinum-resistant or platinum-refractory ovarian cancer [ 20 ]. Olvi-Vec was administered via a temporary intraperitoneal dialysis catheter as 2 consecutive daily doses (3×10 9 pfu/d) followed by platinum-doublet chemotherapy with or without bevacizumab.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…VIRO-15 is the phase 2 study of clinical activity of olvimulogene nanivacirepvec (Olvi-Vec)-primed immunochemotherapy in heavily pretreated patients with platinum-resistant or platinum-refractory ovarian cancer [ 20 ]. Olvi-Vec was administered via a temporary intraperitoneal dialysis catheter as 2 consecutive daily doses (3×10 9 pfu/d) followed by platinum-doublet chemotherapy with or without bevacizumab.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In the non-randomized phase 2 study, the overall response rate was 54% (95% CI: 33-74%), with 8% achieving a complete response, 46% achieving a partial response, and 33% having stable disease. Tumor studies showed significant upregulation of cytotoxic T cells (p = 0.008) [53]. A phase 3 randomized trial is underway (NCT05281471).…”
Section: Oncolytic Viruses (Table 8)mentioning
confidence: 99%